Individual monitoring of occupational external radiation in radiation workers of medical institutions in Jing’an District, Shanghai - KUANG Yujie; XIAO Hong; GAO Linfeng; WANG Bin; LU Shunqi (Shanghai yufang yixue)
ObjectiveTo analyze the individual monitoring results of the radiation workers in Shanghai’s Jing’an District from 2017 to 2023, to assess the occupational protection status as well as to offer scientific references for enhancing occupational health and radiation safety, and to provide support for health education initiatives targeting radiation workers.MethodsRadiation workers from several medical institutions in Jing’an District from 2017 to 2023 were selected as the subjects for this study. The individual dose of occupational external radiation exposure was monitored by using thermoluminescence dosimeters. Continuous data of seven years were statistically analyzed using SPSS 20.0.ResultsFrom 2017 to 2023, the annual collective effective dose for radiation workers in Jing’an District was 329.53 person·mSv, with an average individual annual effective dose of 0.17 mSv, and the median individual annual effective dose was 0.12 mSv. There were statistically significant differences in the individual annual effective doses across different years (H=277.131, P<0.05). The individual doses varied significantly among different levels of medical institutions (H=46.097, P<0.05), with tertiary institutions having the lowest median individual dose of 0.09 mSv, which was significantly lower than those at primary, secondary, and ungraded institutions (P<0.05). The median annual effective dose in males was lower than that in females, showing a statistically significant difference (Z=-3.438, P<0.05). There were significant differences in the individual annual effective doses among different occupational categories (H=150.727, P<0.05), with nuclear medicine workers experiencing the highest median annual dose of 0.56 mSv.ConclusionFrom 2017 to 2023, the individual dose of radiation workers in medical institutions in Jing’an District of Shanghai remained at a low level, reflecting the effective measures of radiation protection facilities in workplaces in Jing’an District, but particular attention should be given to radiological workers in nuclear medicine and workers in primary medical institutions.